General Formula for limit of square function at infinity - Wibowo, Bonno Andri; Maulidi, Ikhsan; Erliana, Windiani (Desimal: Jurnal Matematika, 2018)
Determination of the limit value of a function is an important things. Basically, the limit is used to look at the "properties" function value around the point. In this paper, we provide the general formula for the limit of square root function at infinite. This general formula comes from the development of a commonly known base formula. We use some simple algebra theorems to develop it. The result is very similar to the basic formula for limit of square root function at infinite.